Eksistensi Budaya Sesajen pada Pernikahan Adat Jawa Studi Kasus Dusun Bantan Kecamatan Torgamba Kabupaten Labuhan Batu Selatan - Lestari, Indah; Kamaluddin, Kamaluddin; Ekowati, Endang (Lembaga Yasin AlSys, 2023)
The problem studied in this research is the existence of the culture of offerings, the views and meaning of offerings for the people of Bantan Hamlet in traditional Javanese weddings among the people of Bantan Hamlet, Torgamba District, South Labuhan Batu Regency. From this problem formulation, there is a sub-discussion in it, including a discussion of the opinions of traditional leaders, religious leaders and the community regarding the culture of offerings in Bantan Hamlet. In this research, researchers used qualitative research with a field research design with data collection through observation, documentation and interviews. Meanwhile, the theory used in this research is phenomenology. From the results of this research, it was found that the existence of Javanese traditional wedding offering culture has existed for a long time and this culture has been passed down from the ancestors and passed down to the current generation. The meaning of offerings is thanksgiving for providing smoothness or repelling bad luck in carrying out the wedding ceremony. As well as a form of respect or gift to those who have contributed to the wedding event.